2022
DOI: 10.3390/genes13040574
|View full text |Cite
|
Sign up to set email alerts
|

RNA Sequencing of Whole Blood Defines the Signature of High Intensity Exercise at Altitude in Elite Speed Skaters

Abstract: Although high altitude training has been increasingly popular among endurance athletes, the molecular and cellular bases of this adaptation remain poorly understood. We aimed to define the underlying physiological changes and screen for potential biomarkers of adaptation using transcriptional profiling of whole blood. Seven elite female speed skaters were profiled on the 18th day of high-altitude adaptation. Whole blood RNA-seq before and after an intense 1 h skating bout was used to measure gene expression ch… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…A 24-h long resting period almost completely reversed the gene activation pattern generated by exercise load. These observations together with the results of a recent study ( 22 ) suggest that whole blood RNA-seq is a useful tool for monitoring physiological effects of various exercise programs, albeit further studies are needed to confirm this assertion. Application of ImSig set of immune cell gene signatures helps to investigate immune cell type-specific gene expression changes associated with the response to endurance exercise.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…A 24-h long resting period almost completely reversed the gene activation pattern generated by exercise load. These observations together with the results of a recent study ( 22 ) suggest that whole blood RNA-seq is a useful tool for monitoring physiological effects of various exercise programs, albeit further studies are needed to confirm this assertion. Application of ImSig set of immune cell gene signatures helps to investigate immune cell type-specific gene expression changes associated with the response to endurance exercise.…”
Section: Discussionmentioning
confidence: 74%
“…These observations are consistent with the results of a recent study. Glotov et al ( 22 ) applied whole blood RNA-seq to seven elite female skaters, to assess the immunological and metabolic effects of high-altitude adaptation. They found that inflammatory and immune pathways dominated the observed changes, and on a cellular level, neutrophil degranulation accounts for a substantial fraction of upregulated genes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there have been previous studies that the number of WBC decreased as a result of LHTH training, it is generally reported that the activation of white blood cells is increased by excessive exercise and high-intensity training rather than the effect of altitude [80][81][82]. Platelets play an important role in blood coagulation and hemostasis and living at altitude and vigorous exercise can increase the number of platelets, and excessive increase in the number of platelets can increase bleeding tendency or cause thromboembolism [83,84]. Conversely, acute high-altitude exposure may decrease platelets but return to normal with a compensatory effect after short-term adaptation [85,86].…”
Section: Changes In Cbc and Epomentioning
confidence: 99%
“…These results indicated a role for PHOSPHO1 in stress-related energy metabolism. The expression of PHOSPHO1 was increased in blood samples from athletes with high-altitude training and vigorous intensity exercise ( Glotov et al, 2022 ). Given that hypoxia causes stress erythropoiesis ( Wang et al, 2021 ), Whether PHOSPHO1 regulates energy metabolism in high-altitude adaptation-induced erythropoiesis remains to be explored.…”
Section: Introductionmentioning
confidence: 99%